Finding answers, improving outcomes: a case study of the Canada fetal alcohol spectrum disorder research network. Issue 1 (10th December 2018) - Badry, Dorothy; Coons-Harding, Kelly D.; Cook, Jocelynn; Bocking, Alan
Abstract : Purpose: The purpose of this paper is to present a profile of the Canada fetal alcohol spectrum disorder (CanFASD) research network which is descriptive in nature and profiles the work of the network and its national activities. CanFASD is a unique Canadian, non-governmental organization whose aim is to engage cross-disciplinary research and knowledge translation for stakeholders and partners including communities, policy makers and governments. Design/methodology/approach: A case study approach was undertaken to describe the network whose main focus and purpose is specifically research related to FASD. Findings: The creation of CanFASD has contributed to a strong network of researchers on key topic areas including diagnosis, prevention, intervention, justice and child welfare, with a focus on evidence-based decision making, research and knowledge exchange. A key role of the network is to provide access to research and education on FASD nationally. Research limitations/implications: A case study approach, while descriptive, does not provide the details of specific research projects. Originality/value: CanFASD has had a key role in stimulating meaningful dialogue and research in the field of FASD. The need exists to collaboratively work on a national and international basis in response to the distinct challenges posed by FASD for individuals, families and society.